Mechanical performance of intelligent asphalt mixture utilizing rejuvenator encapsulated method - Sari Sharif Ali; Mahyar Arabani; Hassan Latifi (Fracture and Structural Integrity)
In this study, in order to evaluate the effects of heavy vacuum slops (H.V.S) as rejuvenator and nano-Zycosil as an anti-stripping agent on used encapsulation method and mechanical performance of asphalt mixture samples, scanning electron microscopy (SEM), computerized tomography (CT) scan and thermal gravimetric (TG) analyses and also, indirect tensile strength (ITS) and indirect tensile fatigue (ITF) tests were performed. First, an encapsulation procedure to prepare different specimens including modified and unmodified samples with nano-Zycosil was done. In the following, morphology of the nano-Zycosil-modified capsules and aggregates were particularly evaluated. Considering the morphology evaluation and TG analysis diagrams, it was found that most of the capsules resisted the mixing procedure of the asphalt mixture. So, the encapsulation procedure used in this study was a successful technique. In addition, modification with nano-Zycosil as an anti-stripping agent significantly improved the adhesion strength in the matrix of capsules-aggregates-asphalt binder by converting the adhesion type from silanolian to siloxane. Overall, modification of capsules and main aggregates together with nano-Zycosil significantly improved moisture resistance and mechanical performance of asphalt mixture samples.